PENINGKATAN KOMPETENSI GURU MELAKSANAKAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DENGAN TEKNIK BIMBINGAN BERKELANJUTAN PADA GURU SMK NEGERI 3 KOTABUMI TP 2019/2020 - Mulyani, Sri (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The purpose of this research is to improve the competence of implementing learning through supervision with continuous guidance techniques for teachers of SMK Negeri 3 Kotabumi Academic Year 2019/2020. This school action research was designed in two cycles, from the stages of planning, implementation, observation, and reflection. The subjects of this study were teachers of SMK Negeri 3 Kotabumi, North Lampung, with 6 teachers in each subject. The results of implementing academic supervision with continuous guidance techniques can improve teacher competence in implementing learning at SMK Negeri 3 Kotabumi Academic Year 2019/2020.